144 Head and Neck Cancer and the COVID-19 Pandemic: Impact on Presentation and Management. (19th August 2022) - Maqsood, R; Flynn, W; Douglas, C
Abstract: Introduction: We aim to establish if the first wave of COVID-19 has caused HNC patients to present later or with more advanced disease and if there have been delays in time to imaging, treatment or MDT discussion. Method: Patients were identified retrospectively from a database of cases discussed at head and neck MDT between June and October of 2019 and 2020. New HNC cases were included, and benign or recurrent disease excluded. Data was extracted from electronic patient records and statistical comparisons were performed using JASP. Results: Data was analysed from 216 patients (2019 n=98, 2020 n=118). No statistically significant differences were observed in age, ECOG, smoking and alcohol use. Significantly more patients presented with >6 weeks history of red flag symptoms in 2020 than 2019 with an odds ratio (OR) of 2.44 (95% CI, 1.38 to 4.23), (p=0.002). Patients in 2020 were also significantly more likely to present as an emergency, OR 5.94 (95% CI 1.31 to 27.02), (p=0.013). The OR of being in a higher AJCC stage in 2020 versus 2019 was 1.69 (95% CI, 1.00 to 2.84), (p=0.05). There were no significant differences in time to MDT discussion, first dedicated imaging, or time to initiation of treatment. Conclusion: This data supports concerns that COVID-19 has caused delays in patient presentation, evidenced by longer symptom duration, higher AJCC stage and more emergency presentations. The management was not impacted. HNC services are functioning well despite the pandemic and patients should be encouraged to present to facilitate earlier intervention.